Development of Picture Card Learning Media to Improve Sexual Understanding in Group B Kindergarten Children - Ni Made Putri Widiarsini; Putu Rahayu Ujianti; Mutiara Magta (Indonesian Journal Of Educational Research and Review, 2021)
The rise of cases of sexual violence that occurs in minors causes victims to cause negative reactions such as shame, anger, hatred, offense, and psychological disorders. This study aimed to use picture card learning media to increase sexual understanding in early childhood. This type of research was development research. The model used in the study was the ADDIE model, which consisted of five steps, analysis, design, development, implementation, and evaluation. The techniques used in collecting data were observation, interviews, and questionnaires. The instrument used to collect data was a questionnaire. The data analysis method used was the descriptive quantitative analysis technique. The material expert validity test was carried out with one material expert and one learning media expert. The study results were the assessments given by subject matter and learning media experts. The image media developed were very well qualified. It could be concluded that the picture card learning media was appropriate to be used as a learning media because it could increase students' enthusiasm and motivation in learning to increase children's understanding of sexuality. This research implied that the developed media could be used by teachers in increasing sexual understanding in early childhood.